1985
DOI: 10.1139/v85-498
|View full text |Cite
|
Sign up to set email alerts
|

New functionalized water-soluble benzophenones: a laser flash photolysis study

Abstract: Two water-soluble ionic benzophenones containing a quatemized amine and a sulphonate group have been investigated by laser flash photolysis. The decay kinetics and spectra of their triplet states were studied and quenching constants by triethanolamine, isopropanol, and methyl viologen determined. These data are of interest when these benzophenones are used as initiators for photo-polymerizing water-soluble acrylates in homogeneous solution or in reverse micellar assemblies. The high water solubility of these c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 19 publications
5
11
0
Order By: Relevance
“…From the first-order rate constants, the triplet lifetimes in the absence of oxygen were determined giving values ranging from 12 to 342 μs (Table ), which are in good agreement with the values obtained from the spectroscopic studies (Table ). Furthermore, the obtained values of benzophenone and 4-benzoylbenzoic acid are comparable with the literature. ,, The results show that benzophenone and 4-benzoylbenzoic acid are independent of the analysis wavelength, while xanthone has different decay rate constants at the respective wavelengths. From the spectroscopic studies, it was found that the excited triplet state of xanthone absorbs at higher wavelengths.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…From the first-order rate constants, the triplet lifetimes in the absence of oxygen were determined giving values ranging from 12 to 342 μs (Table ), which are in good agreement with the values obtained from the spectroscopic studies (Table ). Furthermore, the obtained values of benzophenone and 4-benzoylbenzoic acid are comparable with the literature. ,, The results show that benzophenone and 4-benzoylbenzoic acid are independent of the analysis wavelength, while xanthone has different decay rate constants at the respective wavelengths. From the spectroscopic studies, it was found that the excited triplet state of xanthone absorbs at higher wavelengths.…”
Section: Resultssupporting
confidence: 84%
“…Furthermore, the obtained values of benzophenone and 4benzoylbenzoic acid are comparable with the literature. 86,98,99 The results show that benzophenone and 4-benzoylbenzoic acid are independent of the analysis wavelength, while xanthone has different decay rate constants at the respective wavelengths. From the spectroscopic studies, it was found that the excited triplet state of xanthone absorbs at higher wavelengths.…”
Section: F H I Oomentioning
confidence: 96%
“…This is well supported by the fact that the benzenesulfonyl radical is known to exhibit an absorption up to 500 nm. 24 In DETX/CBr4, a residual absorption is also clearly observed at approximately 430 nm. By analogy with the above-mentioned lines of thought with regard to DETX/ BMPS, the formation of a Br' radical may be expected in the sequence of reactions:…”
Section: Resultsmentioning
confidence: 94%
“…The DPK radical formation mechanism in aqueous solutions has been a question for many years. A thermochemical calculation indicated the direct hydrogen abstraction of the BP triplet from a H 2 O molecule could be energetically feasible, but the reaction rate has an upper limit of only ~10 3 M –1 s –1 . Assuming the DPK radical has the same Raman intensity under the same concentration in IPA and in aqueous solution, comparison of the 3‐Cl‐DPK radical Raman spectra in IPA and in a MeCN:H 2 O/1:1 mixed solvent obtained under the same experimental conditions suggests that the yield of the 3‐Cl‐DPK radical is only about 0.09 in the MeCN:H 2 O/1:1 solvent (see supplemental information for details).…”
Section: Resultsmentioning
confidence: 99%
“…A thermochemical calculation [41] indicated the direct hydrogen abstraction of the BP triplet from a H 2 O molecule could be energetically feasible, but the reaction rate has an upper limit of only~10 3 M -1 s -1 . [42,43] Assuming the DPK radical has the same Raman intensity under the same concentration in IPA and in aqueous solution, comparison of the 3-Cl-DPK radical Raman spectra in IPA and in a MeCN:H 2 O/1:1 mixed solvent obtained under the same experimental conditions suggests that the yield of the 3-Cl-DPK radical is only about 0.09 in the MeCN: H 2 O/1:1 solvent (see supplemental information for details). This result suggests that the 3-Cl-DPK radical formation rate in a MeCN:H 2 O/1:1 solvent is~3.6 Â 10 4 M -1 s -1 , which is faster than the predicted limit but much slower than the hydrogen abstraction rate of the BP triplet from IPA (2.3 Â 10 6 M -1 s -1 ).…”
Section: Reactions Of Chloro-substituted Bp Derivative Triplets In Watermentioning
confidence: 99%